The creative co-design of collective spaces. Two case studies of generating new Spatial and Social Infrastructures - Contato, Annalisa; Ronsivalle, Daniele (TeMA - Journal of Land Use, Mobility and Environment, 2025)
In recent decades, the education of minors has been compromised by high rates of educational poverty, further exacerbated by the COVID-19 pandemic. This situation reduces the effectiveness of social infrastructure – the fourth pillar of infrastructure alongside green, blue, and grey infrastructures – that underpins the welfare of national and local entities and encompasses the spaces and artifacts that host social, cultural, and economic activities. The “P.arch. Playground per architetti di comunità” project (P.arch. Playground for Community Architects), aimed at addressing educational poverty, has piloted an innovative educational pathway based on creative activities and engagement with territories and communities from an inclusive and regenerative perspective. The P.arch project involved schools in socio-economically fragile contexts in Sicily and Lazio regions, developing four modules, including “Creative Architecture,” which enabled students to design public and school spaces. Through these activities, new shared spaces and Community Hubs were created to promote social inclusion and community education. Students acquired both cognitive and non-cognitive skills, contributing to an innovative model of community development. This contribution, therefore, highlights the importance of educational processes for generating new connections within the social infrastructure system. It aims to demonstrate how active education and youth engagement are essential for addressing educational poverty and fostering social well-being.